WILL E-COMMERCE COMPLETELY REPLACE TRADITIONAL RETAIL MARKET IN UPCOMING YEARS? (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Shopping behavior has changed considerably in the last decade, retailers find the way to customers preferences through technologies. More than 300% boost happened in e-commerce between 2014-2024 throughout the whole world. Online retail market is replacing traditional retail market steadily even most people cannot notice the change in the shopping. The research investigates what is happening in retail market especially global e-commerce right now and if the situation continuous the same in the following years what is the future of retail market. Both secondary and primary research shows that e-commerce will dominate in the future and it really depends on technology. This scenario is expected to occur in developed countries in the near future and it will take several decades in developing and undeveloped countries